Impact of Long-Period Ground Motions on Structural Design: A Case Study for Bucharest, Romania - Pavel, Florin (SpringerBriefs in Geotechnical and Earthquake Engineering,, 2018)
This book discusses the impact of long-period ground motions on structural design using the situation in Bucharest, the capital city of Romania, as a case study. The first part explores the seismic hazard situation in Bucharest, and the causes of long-period ground motions related to both the source and the site. Subsequently, it examines the current seismic design, detailing building practices in Bucharest, and discusses the impact of long-period ground motions on seismic design. Lastly, several case study buildings in Bucharest are presented and the major difficulties encountered in their design are considered. The book also includes various numerical examples that help readers understand the impact of long-period ground motions on various structural systems, that are currently used in Bucharest. This book is intended for researchers in the field of seismic hazard and risk assessment and designers of multi-story buildings in seismic areas.